Effect of Fructose on Preparation of Nanocrystalline Zirconium Nitride Powder by Internal Gelation Combined with Carbothermic Nitridation. (November 2019) - Zhao, S J; Ma, J T; Deng, C S; Lin, X P; Cheng, X; Hao, S C; Zhao, X Y
Abstract: Nanocrystalline zirconium nitride (ZrN) powder was prepared by using internal gelation combined with carbothermic nitridation. As a carbon source, fructose was added in the internal gelation process to facilitate a homogeneous dispersion. Fructose was decomposed and ultrafine carbon was generated in-situ at high temperature. The ultrafine carbon acted as a reducing agent to remove oxygen atoms in carbothermic nitridation process. The effects of fructose on phase composition, morphology, grain size and specific surface area were analysed. The carbothermic nitridation led to a peculiar morphology in the powder particles. The sample with maximum content of ZrN (88.5%) can be obtained when C/Zr = 1.5. And sample with highest specific surface area (237.6 m 2 /g) can be realized when C/Zr = 2.